A study on assessment of knowledge, attitude and practice on handwashing among nursing students of Sree Venkateswara College of Nursing, Chittoor, Andhra Pradesh - Muthyala, Sudhakara Reddy; Vankayalapati, Venkateswarlu (International Journal Of Community Medicine And Public Health, 2019)
Background: Handwashing is the act of cleaning one's hands for the purpose of removing soil, dirt & microorganisms. Through review of literature it is understood that the most nosocomial infections are thought to be transmitted by the hands of healthcare workers, handwashing is considered the single most important intervention to prevent nosocomial infections. This study was conducted to assess the knowledge, attitude and practices (KAP) on handwashing among the nursing students and to identify the areas of gap in their KAP along with the provisions for handwash. Methods: A descriptive, cross-sectional study was conducted among 192 nursing students at S.V. College of Nursing, Chittoor during October 2018 using pre-validated self-reported questionnaire. Statistical analysis was done with SPSS 20.0 software and Chi-Square test was used with “P” value<0.05 taken as statistically significant. Results: Among all respondents 85% were aware about washing their hands during all common critical times, but practicing was observed in 08% only. 50% felt that alcohol based handrub is effective than handwashing with soap and water, but facilitated 10% only. While the final year students all (100%) were well aware about all critical times of handwashing, whereas 1st and 2nd years 71% and 3rd year students 87% were aware (p=0.002). Conclusions: There is a need of orientation and arrangements for proper handwashing to be improved.